Jedem do Čechách: k nahrazování jmenných koncovek genitivu lokálem - Hrdlička, Milan (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
The form of Czech in a foreign language environment depends on numerous linguistic as well as non-linguistic factors. A common aspect of foreign forms of Czech is its convergence to the local dominant language. Three basic results of language contact are: adoption, reduction and atrophic changes. Foreign forms of Czech are often characterized by quite prevalent replacing of nominal genitive ending with locative, especially in plural. This phenomenon is rooted in dialects; the cause could also be the low acoustic distinctiveness of the genitive ending which is replaced with the phonetically more distinct locative ending.
Keywords: language contact; foreign forms of Czech; declension; genitive; locative; dialects